U.S. Military Information Operations in Afghanistan Effectiveness of Psychological Operations 2001-2010 - Munoz, Arturo (RAND Corporation, 2012)
The U.S. Marine Corps, which has long recognized the importance of influencing the civilian population in a counterinsurgency environment, requested an evaluation of the effectiveness of the psychological operations element of U.S. military information operations in Afghanistan from 2001 to 2010 based on how well messages and themes were tailored to target audiences. This monograph responds to that request.